Supply Chain Integration Researches: An Overview of the Field - ThaÃs Spiegel; Priscila Elida de Medeiros Vasconcelos; Daise Lopes Porto; Heitor Mansur Caulliraux (International Journal of Supply Chain Management, 2014)
The evolution of the logistics concept to a view of the supply chain was based on multi-organizational perception, which gave rise to the idea that a particular company depends, directly or indirectly, on other organizations. Such dependency relationship also indicates that increased competitiveness depends essentially on an integrated performance. In this context, the purpose of this study is to present an overview of the research field, its evolution over time and the main aspects discussed. This paper present a systematic mapping of publications related to the integration of supply chains, a synthesis of the same based on bibliometric indicators and, finally, the survey of the major issues discussed, based on a reference tracking.